Retrospective study of lameness in beef cattle in northeastern Sardinia, Italy - Morrone, Sarah; Scanu, Antonio; Gerolamo, Masala; Crovace, Alberto Maria; Romeo, Stella Maria Teresa; Saderi, Laura; Sotgiu, Giovanni; Columbano, Nicolò (PloS one, 2023)
Lameness is one of the most prevalent diseases affecting dairy and beef cattle, resulting in decreased animal performance, decreased animal welfare, and substantial economic loss. In extensive beef cattle farming, the risk factors for this multifactorial disease are largely unexplored. This study aims to conduct a preliminary epidemiological survey of risk factors in beef cattle in extensive breeding, evaluate the farmer’s perception of lameness, and determine the recurrence frequency of the pathologies under investigation in treated animals. The study was conducted in Sardinia, Italy. The population of the study consisted of 14379 cattle from 230 farms. An ad hoc questionnaire was developed to collect all the necessary data. A strong association was found between breed and the occurrence and recurrence of lameness (p < 0.0001). In addition, the Country of origin of both bulls and cows was found to be correlated with the incidence of lameness (p < 0.0001 and 0.0001, respectively). Farmers who indicated on the questionnaire that lameness was not important on their farm had more animals with recurrences (p < 0.0001) than other farmers. The veterinarian’s treatment choice differed significantly by farmer concern (p = 0.007) and was associated with less disease recurrence (p < 0.0001), resulting in greater farmer satisfaction (p < 0.007). Pure cow breed, French bull origin, and farmer’s age were detected as significant predictors of lameness issues, with pure cow breed and French bull origin having the strongest associations (p = 0.009). Even though the results of this study are preliminary, they indicate that breed selection is crucial in extensive beef farms to reduce lameness prevalence. In addition, it would be reasonable to train breeders to prevent and diagnose lameness early in order to collaborate with veterinarians to prevent recurrence.